SIMULATION OF PHOTOCATALYTIC PHENOL DEGRADATION USING TIO2 P25-BASED PHOTOCATALYST - Jaya Pranata, Jeffry
Phenol waste treatment is one of the most vital unit in polymer, coal gasification, refinery, and coke industry. One way to treat phenol waste is through photocatalysis. This technology is developed because it is more environmental friendly, cheaper, and may use renewable energy as its source. Semiconductor is the most common material used as photocatalysts because the energy from UV and visible light sources are enough for electrons excitation from its valence band to its conduction band. Titanium dioxide (TiO2) P25 is one of the most common and commercialized photocatalysts used for wastewater treatment because of its stability and performance. PHOTOREAC is a MATLAB-based application which can simulate photocatalytic degradation with visible light source. PHOTOREAC is obtained from Professor Miguel Mueses (Cartagena University, Colombia). PHOTOREAC application is used to simulate photon absorption inside the photoreactor and simulate degradation kinetics to determine the best fit kinetic model. The purpose of this study is to find out the influences of operating conditions and TiO2 P25 characteristics on the performances of phenol waste degradation through the photocatalytic process and find the best fitting kinetic model for phenol degradation using TiO2 P25. From the result of simulation and secondary data analysis, pH of the solution has the most significant effect to photocatalytic activity. The optimum pH of the solution to degradate phenol using TiO2 P25 is 7. The optimum photocatalyst concentration for reactor volume of 25-60 mL is 0 – 10 g/L. The optimum photocatalyst concentration for reactor volume of 100 mL is 0 – 5 g/L. Volume of the phenol wastewater and light intensity affect the efficiency of degradation. Bubbling and mixing is critical to maintain oxygen supply because oxygen is needed to form radical compound. The best fitting kinetic model for phenol degradation using TiO2 P25 is Ballari’s kinetic model.